Problematika Guru Kelas V Dalam Penerapan Pembelajaran IPA Terintegrasi Dengan Nilai-Nilai Keislaman Di Madrasah Ibtidaiyah - Nasir, Muhammad; Minarno, Eko Budi; Sholeh, Ahmad (Universitas Muhammadiyah Mataram, 2025)
Abstract: This study aims to analyze the problems faced by fifth-grade teachers in integrating Islamic values into the teaching of Natural Science (IPA) in Madrasah Ibtidaiyah (MI). The integration of science between Islam and IPA is an important aspect, as stated in KMA No. 450 of 2024. Through this decision, learning in Islamic education institutions not only focuses on the cognitive development of students but also on the formation of students' attitudes and religious character. However, in practice, there are still problems faced by teachers in implementing IPA learning that is integrated with Islamic values. This study employs a descriptive qualitative approach. The subjects of this study are two fifth-grade teachers (V-A and V-B) at MI Roudlotul Uqul. Data collection techniques include observation, interviews, and documentation. The data is analyzed through reduction, presentation of data, and drawing conclusions. Data triangulation is conducted to ensure the validity of the data. The results of this study found that the problems faced by teachers are divided into two factors. The internal factors stemming from the teachers themselves include a lack of understanding of the concept of integration, limited integrative pedagogical competence, and the motivation and teaching habits of the teachers. Meanwhile, the external factors include a lack of facilities and infrastructure, curriculum policies, as well as support from the environment and academic culture in schoolsAbstrak: Kajian Ini bertujuan untuk menganalisis problematika yang dihadapi guru kelas V dalam mengintegrasikan nilai-nilai keislaman pada pembelajaran Ilmu Pengetahuan Alam (IPA) di Madrasah Ibtidaiyah (MI). Adanya integrasi keilmuan antara Islam dan IPA menjadi bagian penting, sebagaimana yang tercantum dalam KMA No.450 Tahun 2024. Melalui keputusan tersebut, Pembelajaran pada satuan Pendidikan Islam tidak hanya berfokus pada perkembangan aspek kognitif siswa, namun juga pada pembentukan sikap dan karakter religius siswa. Namun, pada prakteknya masih terdapat problematika yang dihadapi guru dalam menerapkan pembelajaran IPA yang terintegrasi dengan nilai-nilai keislaman. Kajian ini menggunakan pendekatan kualitatif deskriptif. Subjek dari kajian ini yaitu dua orang guru kelas V (V-A dan V-B) di MI Roudlotul Uqul. Teknik pengumpulan data meliputi observasi, wawancara, dan dokumentasi. Data dianalisis melalui reduksi, penyajian data, dan penarikan kesimpulan. Triangulasi data dilakukan untuk memastikan keabsahan data. Hasil dari kajian ini menemukan bahwa problematika guru terbagi menjadi dua faktor. Faktor internal yang berasal dari personal guru meliputi kurangnya pemahaman guru terhadap konsep integrasi, terbatasnya kompetensi pedagogik integratif, dan motivasi serta kebiasaan mengajar guru. Sedangkan dari faktor eksternalnya meliputi kurangnya sarana dan prasarana, Kebijakan Kurikulum, serta dukungan lingkungan dan budaya akademik di sekolah.